Students’ perceptions and readiness towards mobile learning in colleges of education: a Nigerian perspective - John Gyang Chaka; Irene Govender (South African Journal of Education, 2017)
Access to quality education is becoming a huge challenge in Nigeria, in view of the exponential growth in its population, coupled with ethno-religious crises and other acts of terrorism. A large chunk of the country’s population – about 26% have no access to education, as existing teaching and learning facilities have become inadequate. Some interventions such as e-learning and mobile learning (m-learning) have been explored in other levels of education, particularly universities. In order to explore the viability of m-learning to address the inadequacies of facilities and poor access to quality education, this study ascertains the perceptions of students towards m-learning. A quantitative research design, using a sample of 320 students from three colleges of education, is adopted. Descriptive and regression analysis was performed. Based on the unified theory of acceptance and use of technology (UTAUT) model, the results show that performance expectancy, effort expectancy, social influence, and mobile learning conditions are positively correlated with behavioural intention, and that performance expectancy, effort expectancy, and mobile learning conditions significantly predict students’ intention towards m-learning. The study therefore concludes that students in colleges of education in Nigeria had positive perceptions towards mobile learning and are therefore ready to embrace it.